How to meditate : a practical guide - McDonald, Kathleen; Courtin, Robina (b)
What is meditation? Why practice it? Which techniques are best? How do I do it? The answers to these often-asked questions are contained in this down-to-earth book, making it of enormous value for anyone who wishes to begin and maintain a meditation practice. Written by a Western Buddhist nun with solid experience in both the practice and teaching of meditation, How to Meditate contains a wealth of practical advice on a variety of authentic techniques, from what to do with our minds, to how to sit, to visualizations and other traditional practices. Best of all, McDonald$1 (Bs approach is warm and encouraging. The next best thing to personal instruction!s
Includes index.
Keywords: Meditation -- Buddhism